Analisis Perbandingan Kualitas Produk Dan Harga Pada Marketplace Shopee Dan Lazada: Studi Pada Konsumen Di Kota Bima - Vera Damayanti; Muhajirin Muhajirin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This research aims to determine whether or not there is a difference between product quality and price on the Shopee and Lazada Marketplaces. The research method used was comparative and the sampling technique was carried out using the Rao Purba technique because the population in this study was infinite so that the sample obtained was 96 respondents consisting of 48 respondents using the Shopee marketplace and 48 respondents using the Lazada marketplace. The analysis techniques used in this research are validity tests, reliability tests and Independent Sample t-tests. The results of this research show that there is no difference between product quality and price on the Shopee and Lazada Marketplaces.